The interplay of grandparental investment according to the survival status of other grandparent types - Helle Samuli; Tanskanen Antti O; Pettay Jenni E; Danielsbacka Mirkka (Springer Nature, 2022)
Inclusive fitness theory predicts that grandparental investment in grandchildren aims to maximise their inclusive fitness. Owing to an increasing overlap between successive generations in modern affluent populations, the importance of grandparental investment remains high. Despite the growing literature, there is limited knowledge regarding how the survival status of different grandparent types influences each other's investment in grandchildren. This question was studied by using the Involved Grandparenting and Child Well-Being Survey, which provided nationally representative data of English and Welsh adolescents aged 11-16-years. We applied Bayesian structural equation modeling (BSEM) where grandparental investment in grandchildren was modelled using multi-indicator unobserved latent variable. Our results showed that maternal grandmothers' investment was increased by having a living maternal grandfather but not vice versa. Having a living maternal grandmother was also associated with decreased investment of paternal grandparents while the opposite was not found. These findings indicate that the association between the survival status of other grandparents and the focal grandparents' investment varies between grandparent types.